The South Pacific: The New Global Geopolitical Battleground? - Pasaribu, Nico Daniel; Zaini, Ansori; Alam, Tasdik Mustika (PT FORMOSA CENDEKIA GLOBAL, 2024)
The dynamics of the strategic environment in South Pacific Region involving major powers in the world such as USA, Australia, China, Japan, India, New Zealand, make the world's eyes on the Region. The purpose of this study is to further explain why the South Pacific region is considered a new global geopolitical battleground. This research was developed using the literature study method. The results of the analysis show that this region has a strategic geographic location and has abundant natural resources that make major countries in the world compete to strengthen their influence and dominance in the region in order to achieve their national interests thus making the South Pacific region has become a new battleground in global geopolitics.